State of Our Feminist Movements: The Power of Young Feminist Organizing. Issue 1 (September 2017) - Anumo, Felogene
Abstract At a global level, young feminists experience a myriad of challenges that affect their daily lives and well-being and threaten their organizing. As exposed by the AWID 2016 Forum, young feminists are using ground-breaking strategies to confront some of the most urgent issues of our time, working together with some of the most vulnerable populations. However, they remain extremely under-resourced and their long-term sustainability is at risk. Investing in young feminist organizing is essential to the life of our movements as it creates a pipeline of leaders, diversifies voices, perspectives and deepens inclusivity.